I'd know you anywhere - Lippman, Laura, 1959- (William Morrow, 2010)
Eliza Benedict's peaceful suburban life is shattered after being contacted by Walter Bowman, the man who kidnapped and held her hostage as a teen in 1985, and who now claims to want forgiveness while on death row. An edgy, utterly gripping tale of psychological manipulation.